Spectral studies of transition metal complexes of dihydrobis(1-pyrazoyl)borate with some Lewis bases. Issue 1 (1st January 2016) - Mesubi, Adediran M.; Eke, Uche B.; Oyeku, Oyedele M.; Owalude, Samson O.
Abstract: Co(II), Ni(II) and Cu(II) complexes of dihydrobis(1-pyrazolyl)borate and their adducts with some Lewis bases have been prepared and characterized by elemental analyses, IR and UV–vis spectroscopic techniques. The adducts were either 1:1 or 1:2 complexes depending on whether the Lewis base was bidentate or monodentate. The results indicate that adducts with 1, 10-phenanthroline were the most stable due to the chelating effect of the Lewis base. The order of reactivity of the complexes was determined to be Ni(H2 BPz2 )2  > Cu(H2 BPz2 )2  > CoH2 (BPz2 )2  > Co(H2 BPz2 )2 . The effects of various solvents (i.e., benzene, chloroform and DMF) on the structure were studied. The solvents appear to minimally affect the visible spectra of Co(H2 BPz2 )2 . The Ni(H2 BPz2 )2 and Cu(H2 BPz2 )2 adducts exhibit a four-coordinate structure in non-coordinating solvents. However, in coordinating solvents, such as DMF, the adducts exhibit six-coordinate structures.